Retrospective analysis of the poisoning cases in four different regions of the world - Kordbacheh, Hananeh; Shishani, Lamis F.; Kolci, Kubra; Alomar, Rim; Hamze, Baraa; Aydin, Ahmet (Marmara Univ, Fac Pharmacy, 2025)
ABSTRATC: Poisoning remains a significant public health concern and continues to be one of the primary reasons for hospital admissions worldwide. Therefore, it is crucial to identify the most common causes of poisoning to reduce morbidity and mortality rates. This study aims to summarize and compare the frequency, patterns, causative agents, and gender distributions of poisoning among the most populous countries in the Middle East, North Africa, and South Asia regions, including Turkey, Jordan, Morocco, and India. The paper reviews literature on poisoning cases admitted to emergency departments between 2010 and 2020. A total of 20 relevant papers were included in the study. In Jordan, Turkey, India, and Morocco, 2545, 4441, 2895, and 3462 poisoning cases were identified, respectively. Ingestion was the primary route of exposure. In Jordan and India, the majority of poisoning cases were observed in males, while in Turkey and Morocco, females were more frequently involved. Non-pharmaceutical substances were the main cause of poisoning in Jordan, India, and Morocco, whereas medication was the primary cause of intoxication in Turkey. Except in Jordan, intentional exposure was the most common type of poisoning among the countries. To the best of our knowledge, there is no systematic review comparing the pattern of poisoning in these countries. The data extracted in this study can be utilized to enhance public awareness regarding both medication and non-medication intoxication.
Keywords: Intentional poisoning; Unintentional poisoning; Emergency departments; Frequency of poisoning; Exposure route